Blockchain Encryption on Student Academic Transcripts using a Smart Contract - Primasatria Edastama; Ninda Lutfiani; Qurotul Aini; Suryari Purnama; Isabella Yaumil Annisa (Journal of Educational Science and Technology (EST), 2021)
As an innovation in the world of computers, blockchain has many benefits and is also widely applied in the world of education. Blockchain itself has many advantages, especially in the world of education. Blockchain is a digital data storage system that consists of many servers (multiserver). In this Blockchain technology, data created by one server can be replicated and verified by another server. By using this technology with a decentralized system and strong cryptography and can help colleges or universities to build infrastructure in the archive storage of transcripts, diplomas, and diplomas. Usage One of the blockchain technology applications in education is iBC, namely the e-learning Blockchain Certificate, book copyright, and also e-Portfolios. iBC or e-learning Blockchain Certificate is a tool designed to create, verify and also issue blockchain certificates. As has been supported by the IBC to create certificates that are globally verified and stored in a decentralized manner. Here will be presented use cases that are relevant in the use of Blockchain technology in educational environments, especially data processing in universities and we also try to design an IBC based on blockchain technology that can be used to support transparency and accountability of colleges or universities in issuing diplomas and grades.